Risk factors for premature delivery, literature review - Idawati; Maulisa, Desi; Baiyatun; Agusnita, Eka; Rosida (Trigin Institute, 2023)
Preterm birth is a birth that occurs at 20 to 37 weeks gestation, the main difficulty in preterm labor is the care of premature babies, the younger the gestational age the greater the risk of morbidity and mortality. This study is a literature study by examining 20 journals with the same topic and theme related to risk factors for preterm labor. After analysis, there are 5 relevant journals. Literature review shows that factors that influence prematurity refer to. history of gynecological diseases, disruption of the uterus due to too high parity, the influence of education, lack of awareness and unplanned mindset, as well as irregular eating patterns and unhealthy lifestyles, malnutrition and anemia and neonatal infections.